THE INFLUENCE OF SOCIAL CAPITAL ON FACULTY PERFORMANCE - Yuliana Sri Purbiyati; Lydia Ari Widyarin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Social capital has been studied by experts for decades. So many studies and discussions that state there is support for an object or vice versa. This study tries to uncover the effect of social capital on the performance of a faculty at a university. There are ten hypotheses for this study. data was taken with a questionnaire as primary data and observations as secondary data. Data analysis was carried out with smartPLS. Of the seven hypotheses of direct influence, five hypotheses were found to be proven between the independent variable and the dependent variable to have a positive and significant relationship. Two of the seven hypotheses of direct influence there are two hypotheses whose results have a positive and insignificant effect. For variables with an indirect effect from the three hypotheses, there are two hypotheses that have a positive and insignificant relationship. One variable that has a positive and significant relationship between the independent and dependent variables through the mediating variable is CSC on the EDP variable through LICV. Keywords: Structural social capital, Relational social capital, Cognitive social capital, faculty performance, leadership and core values